Enhanced nematicidal potential of MnCl2-fortified Bacillus sp. cell-free supernatant against Meloidogyne incognita - Dyah Retno Anggraini; Dyah Ayu Savitri; Mochammad Wildan Jadmiko; Sofia Sofia; Sudarko Sudarko; Yuli Hariyati; Khaerani Nurlaelita; Ankardiansyah Pandu Pradana (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2026)
Meloidogyne incognita causes major yield losses, underscoring the need for sustainable control strategies. This study is the first to demonstrate that micronutrient fortification and pH modulation of Bacillus sp. SK07 cultures enhance the nematicidal activity of their cell-free supernatant (CFS) and alter metabolite composition. Bacillus sp. SK07 was cultured in Nutrient Broth supplemented with MnCl2 at 0, 50, or 75 ppm, with pH adjusted to 6 or 8. A 10% (v/v) CFS was evaluated in vitro against eggs and second-stage juveniles (J2) over 7 days using a completely randomized design with five treatments and five replicates. The most effective treatment—50 ppm MnCl2 at pH 8—resulted in 96.4% egg-hatch inhibition and 63.6% J2 mortality at 168 hours, significantly higher than the unfortified control (91.8% and 49.4%, respectively). Chemical analysis revealed substantial changes in metabolite composition: unfortified cultures exhibited 9 peaks, whereas the optimized treatment produced 27 peaks, indicating increased chemical diversity. Several bioactive compounds, including fatty acid derivatives and aromatic esters, were identified. These compounds belong to diverse chemical classes such as acids, esters, alcohols, and hydrocarbons, many of which are known for their nematicidal activity. These findings demonstrate that MnCl2 fortification at pH 8 effectively enhanced the bioactivity of Bacillus sp. SK07, offering a promising and sustainable approach for managing M. incognita.